Active MMP-8 as a Biomarker of Peri-implant Health or Disease - Xanthopoulou, Vithleem; Räisänen, Ismo; Sorsa, Timo; Sakellari, Dimitra (European Journal of Dentistry, 2022)
Objectives This study investigated the potential of testing for active matrix metalloproteinase-8 (aMMP-8) by a quantitative point-of-care (PoC), chairside, lateral flow immunotest as a biomarker for the presence or absence of peri-implant diseases.Materials and Methods Eighty healthy patients with implants were recruited. The samples were collected from peri-implant sulcular fluid and quantitatively analyzed for aMMP-8. Clinical indices, which included probing depth, clinical attachment loss, bleeding on probing, and plaque, were recorded and radiographic assessments were performed.Statistical Analysis Comparisons of aMMP-8 levels and clinical parameters were analyzed by the Kruskal–Wallis test and the pairwise post hoc Dunn–Bonferroni test. A receiver operating curve analysis was used to analyze the diagnostic ability of aMMP-8 and the correlation between aMMP-8 and probing depth of the sampled site was sought by Spearman's rho and the coefficient of determination (R2).Results Statistical analysis revealed statistically significant differences of aMMP-8 levels between the healthy and the mucositis and peri-implantitis groups, and between the mucositis and the peri-implantitis groups. Increasing probing depths of the sampled site and aMMP-8 levels were significantly correlated.Conclusions These data suggest that the aMMP-8 PoC test can be a beneficial adjunctive tool for early identification and screening of the risk of peri-implant diseases and progression.
Keywords: aMMP-8; peri-implant health; peri-implant disease